Tuberculosis-like respiratory infection in 245-million-year-old marine reptile suggested by bone pathologies - Dawid Surmik; Tomasz Szczygielski; Katarzyna Janiszewska; Bruce M. Rothschild (Royal Society Open Science, 2018)
An absence of ancient archaeological and palaeontological evidence of pneumonia contrasts with its recognition in the more recent archaeological record. We document an apparent infection-mediated periosteal reaction affecting the dorsal ribs in a Middle Triassic eosauropterygian historically referred to as ‘Proneusticosaurus’ silesiacus. High-resolution X-ray microtomography and histological studies of the pathologically altered ribs revealed the presence of a continuous solid periosteal reaction with multiple superficial blebs (protrusions) on the visceral surfaces of several ribs. Increased vascularization and uneven lines of arrested growth document that the pathology was the result of a multi-seasonal disease. While visceral surface localization of this periosteal reaction represents the earliest identified evidence for pneumonia, the blebs may have an additional implication: they have only been previously recognized in humans with tuberculosis (TB). Along with this diagnosis is the presence of focal vertebral erosions, parsimoniously compared to vertebral manifestation of TB in humans.